2017
DOI: 10.1007/s00216-017-0462-z
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of aflatoxins, T-2 and HT-2 toxins, and fumonisins in cereal-derived products by QuEChERS extraction coupled with LC-MS/MS

Abstract: A fast, easy, and cheap method for the simultaneous determination and quantification of aflatoxins (B1, B2, G1, G2), T-2 and HT-2 toxins, and fumonisins (B1, B2) in cereal-derived products was developed. This method involved a quick, easy, cheap, effective, rugged, and safe (QuEChERS) extraction coupled with liquid chromatography-tandem mass spectrometry. The method validation was performed by analyzing samples spiked at four levels, and the recoveries ranged from 83.6 to 102.9%, whereas the maximum values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The European Commission Regulation (1998) has set maximum limits of total AF and AFB 1 at 4 and 2 µg/kg in cereals, respectively. Current detection methods for AF level include thin layer chromatography, enzyme-linked immune sorbent assay, and liquid chromatography-mass spectrometry (Wang et al, 2013;Zitomer et al, 2015;Akhund et al, 2017;Annunziata et al, 2017). The purification of AF by high-performance liquid chromatography-fluorescence detection combined with immunoaffinity column (IAC-HPLC-FLD) has been applied in many complex sample substrates, which is easy to operate and highly sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…The European Commission Regulation (1998) has set maximum limits of total AF and AFB 1 at 4 and 2 µg/kg in cereals, respectively. Current detection methods for AF level include thin layer chromatography, enzyme-linked immune sorbent assay, and liquid chromatography-mass spectrometry (Wang et al, 2013;Zitomer et al, 2015;Akhund et al, 2017;Annunziata et al, 2017). The purification of AF by high-performance liquid chromatography-fluorescence detection combined with immunoaffinity column (IAC-HPLC-FLD) has been applied in many complex sample substrates, which is easy to operate and highly sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…The fungal infestation brings intolerable alterations in appearance, color, texture, flavor, and nutrition of food (Pitt and Hockings, 2009 ). Therefore, the incidence of fungi and mycotoxins contamination in agricultural products have become one of the foremost issues of farmers, food industry, and government concerning the food safety (Annunziata et al, 2017 ; Udomkun et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, the contribution and potential of MS-based techniques were clearly shown as they can detect trace levels of AFM 1 in white cheese because of their high sensitivity. Although there were a number of studies explaining the detection of AFM1 either only LC-MS or LCMSMS only [36][37][38][39][40][41][42][43] , this study showed the detection of AFM1 by these two methods…”
Section: Discussionmentioning
confidence: 64%